Where are primary type specimens of new mite species deposited? - Liu, Jian-Feng; Wei, Xiao-Ying; Li, Guang-Yun; Zhang, Zhi-Qiang (Zootaxa, 2017)
A list of type depositories of new mite species published in two journals (Systematic & Applied Acarology and Zootaxa) during the last five years (2012–2016) is presented in this paper. The 1370 new species are deposited unevenly among 134 collections. The top collection is the Zoological Institute of the Russian Academy of Sciences, St. Petersburg, Russia (145 species), which alone accounts for 10% of the total new species, and the top ten collections accounted for 48% of the total. The average number of new species per collection is 10 and over three quarters of the collections are below the average. Just over half (51%) of the collections are in Europe. However, overall there were still more new species deposited in collections in developing counties (741) than developed countries (629). The top country for type depositories of new mite species for each continent is: Russia (199 species) for Europe, Brazil (134 species) for South America, Iran (133 species) for Asia, Australia (87 species) for Oceania, USA (80 species) for North America and South Africa (36 species) for Africa. The top European collections hold type specimens mostly of foreign origin, whereas those of South America, Asia, Africa and Australasia hold type specimens mostly originating from their own countries.